2013
DOI: 10.1002/bjs.9057
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver disease as a predictor of local recurrence following resection of colorectal liver metastases

Abstract: Hepatic steatosis was an independent predictor of local hepatic recurrence following resection with curative intent of colorectal liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 21 publications
1
47
1
Order By: Relevance
“…We also examined the effect on tumour recurrence of each nafld histologic feature separately and looked into the effect of micro-and macro-steatosis. Hamady et al 69 concluded that liver steatosis is an independent predictor for disease recurrence. On the other hand, Murono et al 70 found that crc-lm occurs less frequently in fatty livers after resection, suggesting that steatosis might provide an unfavourable environment for metastasis in liver.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the effect on tumour recurrence of each nafld histologic feature separately and looked into the effect of micro-and macro-steatosis. Hamady et al 69 concluded that liver steatosis is an independent predictor for disease recurrence. On the other hand, Murono et al 70 found that crc-lm occurs less frequently in fatty livers after resection, suggesting that steatosis might provide an unfavourable environment for metastasis in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Parenchymal abnormalities that occur during liver regeneration independently worsen oncological outcomes [46]. Thus, major hepatectomies with intense post-operative regeneration or segmentectomies that leave parenchyma without adequate venous drainage may not be the best treatment for hepatic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Moderate to severe steatosis (triglyceride content >33% 4 ) and steatohepatitis (steatosis with hepatocyte ballooning, lobular inflammation and fibrosis 4 ) are associated with increased post-operative morbidity (two-fold increase) and peri-operative mortality (2.8-to 10-fold increase). 5,6 Retrospective studies have shown excess body mass index (BMI), diabetes and pre-operative chemotherapy are associated with steatosis and/or steatohepatitis in the resection specimen.…”
Section: Introductionmentioning
confidence: 99%